1998
DOI: 10.1093/oxfordjournals.pcp.a029445
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Cytokinin Up-Regulated Gene from Tobacco Mesophyll Protoplasts

Abstract: We have isolated a cytokinin up-regulated cDNA clone, H13, from an early stage of cultured tobacco mesophyll protoplasts by a differential display method. The expression of this gene was specifically induced by natural and synthetic cytokinins including N-(2-chloro-4-pyridyl)-N'-phenylurea (4PU30), a diphenylurea-type cytokinin, although the simultaneous presence of auxin was also required. It seems that the preceding treatment of the tobacco mesophyll protoplasts by auxin is necessary for the gene to respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, this domain is not characteristic of arabinogalactan proteins (AGPs), and the Pis63 protein is not a typical AGP. In addition, Pis 63 and related genes share an amino acid motif, [(Q/E)(Q/K/R/)QG(M/L/)SDTRFLXNGKX-(Y/X)YD] as described in Iwahara et al (1998), that is present in several reported sequences including AGPNa2, AGPPc2 (Mau et al 1995), E6 (John and Crow 1992), and a cytokinin-upregulated gene (Iwahara et al 1998). …”
Section: Resultsmentioning
confidence: 99%
“…However, this domain is not characteristic of arabinogalactan proteins (AGPs), and the Pis63 protein is not a typical AGP. In addition, Pis 63 and related genes share an amino acid motif, [(Q/E)(Q/K/R/)QG(M/L/)SDTRFLXNGKX-(Y/X)YD] as described in Iwahara et al (1998), that is present in several reported sequences including AGPNa2, AGPPc2 (Mau et al 1995), E6 (John and Crow 1992), and a cytokinin-upregulated gene (Iwahara et al 1998). …”
Section: Resultsmentioning
confidence: 99%
“…Since the probe was feasible for labeling GABA B receptors, we further tested whether the probe could bind to similar GABA receptors on the surface of plant protoplasts. Mature mesophyll protoplasts were isolated according to a previously published protocol (Iwahara et al, 1998); mature pollen protoplasts were also isolated using a germination-enzymatic treatment protocol established in our lab (Yu et al, 2006). Both types of living protoplasts were isolated, collected, and incubated with the probes.…”
Section: Imaging Of Gaba-binding Sites Using Probesmentioning
confidence: 99%
“…Differential display is a polymerase chain reaction (PCR)based procedure for amplifying and comparing messenger RNA (mRNA) populations between two contrasting physiological states, i.e., tissue types, developmental stages, or treated and untreated tissues (Liang and Pardee 1992). The technique has been used to isolate genes whose expression patterns are affected by the phytohormones ethylene (Hajouj et al 2000;Zegzouti et al 1999), abscisic acid (Yoshida et al 2001), cytokinin (Iwahara et al 1998), and auxin (Dargeviciute et al 1998;Hutchison et al 1999). We previously used the procedure to isolate genes associated with early events of seed dormancy maintenance and release (Johnson et al 1995).…”
mentioning
confidence: 99%